Effectiveness of music therapy for children with autism spectrum disorder: meta-analysis and potential biological mechanisms - Wu, Li; Zhang, Xinming; Liu, Shuyue; Gao, Xinping; Wang, Jun (Frontiers in Psychiatry, 2026)
ObjectivesAutism spectrum disorder (ASD) is a complex neurodevelopmental disorder characterized by deficits in social interaction, communication skills, and repetitive behaviors. However, no effective pharmacological treatments targeting core symptoms have yet been developed. As a non-pharmacological intervention, music therapy (MT) is increasingly being explored for its potential value in improving functional outcomes for children with autism. This study aims to examine the efficacy of MT for children with ASD through a meta-analysis.MethodWe conducted a systematic review following the PRISMA guidelines. A comprehensive and systematic search of PubMed, Web of Science, and the Cochrane Library databases up to August 2025 was performed to identify studies on MT treatment for children with ASD. Continuous variables were reported as standardized mean differences (SMD) with 95% confidence intervals (CI). All analyses were conducted using Stata statistical software version 17.0.ResultsOur meta-analysis included 18 studies. Results showed that MT significantly reduced the total score on the Autism Behavior Checklist (ABC) (SMD = -0.76, 95% CI: -1.31 to -0.22, P = 0.01) and Childhood Autism Rating Scale (CARS) total scores (SMD = -0.43, 95% CI: -0.73 to -0.14, P < 0.01). Specifically, compared with the control group, MT significantly improved social skills (SMD = -0.26, 95% CI: -0.46 to -0.05, P = 0.01), behavioral abilities (SMD = -0.72, 95% CI: -1.06 to -0.39, P < 0.01), and sensory (SMD = -0.87, 95% CI: -1.68 to -0.07, P = 0.03), emotional (SMD = -1.31, 95% CI: -1.98 to -0.64, P < 0.01), and verbal functioning (SMD = -0.65, 95% CI: -0.19 to 1.12, P = 0.01).ConclusionIn summary, MT demonstrates efficacy in improving behavioral symptoms associated with autism spectrum disorders. However, caution should be exercised when interpreting results due to limited research literature in some analyses. Further studies are needed to validate its therapeutic effects.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD420251252228.